Pengaruh Perputaran Modal Kerja dan Perputaran Piutang terhadap Profitabilitas pada PT. Indofood CBP Sukses Makmur Tbk yang Terdaftar di BEI Periode 2019-2023 - Diva Ariska Ananda; Anwar Ramli; Andi Mustika Amin; Nurman Nurman; Annisa Paramaswary Aslam (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to analyze the effect of working capital turnover and accounts receivable turnover on profitability at PT. Indofood CBP Sukses Makmur Tbk, listed on the Indonesia Stock Exchange (IDX), during the 2019–2023 period, by examining financial performance reports. The research employs a descriptive design with a quantitative approach. The analysis examines three variables: working capital turnover and accounts receivable turnover as independent variables, and profitability as the dependent variable. The testing is conducted using SPSS Statistics software version 25. The results of the study reveal three hypotheses, with one hypothesis accepted and two rejected. Therefore, it can be concluded that, in this study, only accounts receivable turnover has a significant impact on profitability, while working capital turnover does not affect profitability in the case study object, PT. Indofood CBP Sukses Makmur Tbk.